Penerapan Bimbingan Kelompok Berbasis Teori Karier Holland untuk Meningkatkan Pemahaman Karier pada Siswa SMA Negeri 18 Surabaya: Application of Group Guidance Based on Holland's Career Theory to Improve Career Understanding in Students of SMA Negeri 18 Surabaya - Ramandita, Ferra Berliana; Bakhrudin All Habsy; Nurudducha (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
This study aims to improve career understanding among high school students, especially at SMAN 18 Surabaya, through group guidance based on Holland's career theory. However, many students are still confused in determining a career that suits their personality. Therefore, this study aims to improve students' career understanding through the application of group guidance based on Holland's career theory. This research uses qualitative methods, with the type of Guidance and Counselling Action Research, in this study consisting of three cycles. Each cycle involves the stages of planning, action implementation, observation, and reflection. In the planning stage, the researcher together with the counselling teacher identified the problem and designed the guidance material according to the students' needs. The implementation of the action was conducted through group guidance sessions, where students took the RIASEC test and engaged in group discussions to recognise their personality types and relate them to career choices. The results showed a significant improvement in students' career understanding after attending group guidance based on Holland's career theory. Students were able to recognise their personality type and choose an appropriate career. Group guidance also proved effective in enriching students' understanding and increasing their confidence in career planning. In conclusion, group guidance based on Holland's career theory is effective in improving students' career understanding and assisting them in making more informed career decisions. Keywords: Group Guidance, Holland's Career Theory, Career Understanding